Regression Analysis of The National Cyber Security Index In The Southeast Asia Region - Adityan Wisnu Yuda Prasetya; Bambang Suhardjo; Rinaldy Munir (Pelopor Publikasi Akademika, 2024)
In the current era of the Industrial Revolution 4.0, information and communication technology is rapidly developing in all sectors. In the matrix of non-military defense implementation, technology is one of the dimensions that influence the achievement of a country's general defense policy. Technological development does not always have a positive impact. Cyber threats and attacks are an example of the negative impact in technological development. In the